Neurotechnology and brain stimulation in pediatric psychiatric and neurodevelopmental disorders - Oberman, Lindsay M.; Enticott, Peter G. (Academic Press, is an imprint of Elsevier, 2019)
Neurotechnology and Brain Stimulation in Pediatric Psychiatric and Neurodevelopmental Disorders provides a comprehensive overview of neurotechnological devices as potential treatments for psychiatric and neurodevelopmental disorders in children and adolescents. Many neuropsychiatric disorders are covered such as Autism Spectrum Disorder, ADHD, Depression, Tourette's Syndrome, and OCD. Different device-based treatments are discussed such as Transcranial Magnetic Stimulation, Transcranial Direct Current Stimulation, Deep Brain Stimulation, Chronotherapy, and Neurofeedback.